Kinopravda 20 - Vertov, Dziga (Soviet Union : Goskino, 1925)
Pioneers marching, the youngest pioneers of the factory, the leader of the pioneer unit speaks of excursions to a village and a zoo. Village scenes, fields, peasants working. Children on horses. Street scenes. Village cooperative. Posters advertising cooperative. People taking out goods from cooperative. Village entertainment, dancing, a man playing the harmonica. Excursion to the village: pioneers marching along the main street. A train is going, pans from the movement. Arrival in the station. Komsomol members cut wood for the villagers, pioneers help. Pioneers working in the fields, ploughing. Lunch. Reading newspapers and journals to the peasants. Excursion to a zoo. Pioneers marching, young biologists with animals. Elephant. Children. Kangaroo, Monkeys, other animals. Children are playing with animals.
Recording disturbance on minutes 10-11.
Keywords: Soviet Union